Effects of Compensation and Workplace Motivation on Employee Performance - Sari, Cucu Permata (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
To be able to provide professional staff, high employee performance is expected by the company. Thus this study aims to determine the effect of compensation and motivation on employee performance at PT. Cadets Jaya. This research is a case study with quantitative methods using multiple correlation tests. This research was conducted on Taruma Jaya company employees as many as 50 respondents. The data used in this study are primary data collected through questionnaires using techniques saturated sample. The results of this study indicate that compensation and motivation have a partial and simultaneous effect on employee performance.